Development of an assay for the detection of the federally threatened Florida eastern indigo snake (Drymarchon couperi) using soil eDNA - Carlos A. Santamaria; Emily Galbraith; Alison M. Gainsbury (Conservation Science and Practice)
Abstract Accurate information on species range contraction is the cornerstone of effective biodiversity conservation. The eastern indigo snake (Drymarchon couperi) is an apex predator in Florida and, similar to many species native to Florida, is threatened by widespread habitat destruction. Environmental deoxyribonucleic acid (eDNA) monitoring of this elusive snake would provide a non‐invasive approach to improve our knowledge of the species' range and distribution. We designed and tested an eDNA assay that can detect the presence of D. couperi from soil samples from their natural scrub habitat in Florida. We validated our assay in silico, in vitro, and in situ. Furthermore, we investigated the influence of temperature and humidity on the degradation rate of eDNA over time. We successfully amplified the cytochrome b gene for D. couperi at concentrations as low as 3 × 10−3 ng/μL and successfully detected the presence of D. couperi in 2 of 30 in situ field soil samples. The degradation experiment resulted in detectable DNA for 10 days. Interestingly, temperature and humidity had no effect on the degradation rate of eDNA in our experimental conditions. This study provides support for soil eDNA applications to detect the presence of a federally threatened species in their natural environment bolstering our ability to monitor the conservation and management of imperiled species. Environmental DNA provides an additional conservation tool to quickly and effectively monitor species range shifts driven by multiple anthropogenic stressors to promote the persistence of imperiled species.